2017
DOI: 10.1037/cdp0000133
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination and psychological health among Polynesians in the U.S.

Abstract: Mental health professionals need to be aware of racial discrimination on psychological health and incorporate the value of self-esteem in the psychological treatment of Polynesians. Additional results are provided and implications of these findings are outlined. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
(134 reference statements)
2
11
0
Order By: Relevance
“…For example, Pokhrel and Herzog (2014) found that discrimination mediated the relationship between historical trauma and increased substance use in NHOPI emerging adults. Survey research has also indicated that racial/ethnic discrimination is positively related to mental health concerns and psychological distress among Polynesian emerging adults in the United States (Allen et al, 2017). Additionally, health disparities research has indicated that racism is associated with increased stress and negative health outcomes in Native Hawaiians (Antonio et al, 2016; Kaholokula et al, 2012).…”
Section: Emerging Adulthood and Substance Usementioning
confidence: 99%
“…For example, Pokhrel and Herzog (2014) found that discrimination mediated the relationship between historical trauma and increased substance use in NHOPI emerging adults. Survey research has also indicated that racial/ethnic discrimination is positively related to mental health concerns and psychological distress among Polynesian emerging adults in the United States (Allen et al, 2017). Additionally, health disparities research has indicated that racism is associated with increased stress and negative health outcomes in Native Hawaiians (Antonio et al, 2016; Kaholokula et al, 2012).…”
Section: Emerging Adulthood and Substance Usementioning
confidence: 99%
“…Despite these increasing numbers, Native Hawaiians are often lumped or glossed together with other ethnic groups and assumed to be “Asian-American” (Allen et al, 2016; Trimble & Bhadra, 2013). This assumption is problematic because they are viewed as part of the “model minority stereotype” and their unique psychological needs and experiences with discrimination are overlooked (Allen et al, 2017). Moreover, this group is understudied and underrepresented in discussions of identity, mental health, racism, educational access, and equity (Borrero et al, 2012; Bollinger et al, 2020; Kaholokula et al, 2019), and as a place, Hawai’i (and its schools) reveals the dislocation and isolation that occur as a result of an educational system that focuses on standardized measures prioritizing white, middle-class values and assimilationist individualistic identities (Kana’iaupuni & Ishibashi, 2003).…”
Section: Why Native Hawaiians?mentioning
confidence: 99%
“…Research supports the general health disparities that exist among NHPIs including the highest prevalence rates of obesity, diabetes, and cardiovascular disease in the state of Hawai‘i (Kaholokula, 2017; Kaholokula et al, 2019), the increased likelihood of developing chronic illnesses at a younger age compared to the rest of the U.S. population, and shortening the lifespan by a decade compared to other ethnic groups (Mau et al, 2009). Discrimination has been found to affect NHPIs’ health including increasing risk for hypertension (Ing et al, 2019) and mental health issues such as depression and anxiety (Allen et al, 2017; Ing et al, 2019; McCubbin & Antonio, 2012). This picture of health disparities is further exemplified when comparing NHPIs to Asian Americans.…”
Section: The Colonizer’s Gazementioning
confidence: 99%